Immunoglobulin concentration in gingival tissue of type 2 diabetic patients with periodontitis - Anil Sukumaran (Wolters Kluwer Medknow Publications, 2006)
BACKGROUND: Diabetes mellitus is considered as a risk factor for the initiation and progression of periodontal disease. The diabetic patients often exhibit decreased immune response and increased susceptibility to infection. In the present study, a quantitative estimation of the gingival tissue immunoglobulin concentrations in diabetic and non diabetic subjects with periodontitis was assessed and compared with that of clinically healthy gingiva. METHOD: 40 gingival tissue samples obtained from 20 diabetic (Type 2) and 20 non-diabetic subjects were subjected to quantitative estimation of immunoglobulins G, A, and M. The data thus obtained were compared to the level of immunoglobulin found in clinically healthy gingiva. RESULTS: The IgG and IgA level in the tissues of both diabetic and non-diabetic subjects with periodontitis were found to be significantly higher than that of healthy subjects. The diabetic group also showed a significantly higher IgG and IgA levels compared to the non-diabetic group with periodontitis. CONCLUSION: These findings support the concept that the humoral immune response plays an important role in the pathogenesis of periodontal disease in diabetics. The significantly higher levels of immunoglobulin in the gingival tissues might be a protective mechanism against the increased bacterial challenge in diabetic subjects.